ASSOCIATION BETWEEN TOOT HBRUSHING HABITS AND GINGIVITIS STATUS AMONG HIGH SCHOOL STUDENTS - Cici Maulida; Reca Reca (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: Gingivitis is a common inflammatory condition affecting the gingival tissues, primarily resulting from the accumulation of dental plaque due to inadequate toothbrushing practices. Adolescents are particularly susceptible to this condition because hormonal fluctuations during puberty can intensify the inflammatory response of the gingiva. Findings from a preliminary survey involving 10 tenth-grade students at SMA Negeri 1 Krueng Barona Jaya showed that 50% of the participants experienced mild gingivitis, while 10% had moderate gingivitis. In terms of oral hygiene, 70% demonstrated a moderate level of oral and dental cleanliness, whereas the remaining 30% were categorized as having poor oral hygiene. Furthermore, interview results indicated that bleeding gums during toothbrushing was the most frequently reported complaint among the students. Purpose: This study aimed to determine the relationship between toothbrushing habits and gingivitis among grade X students at SMA Negeri 1 Krueng Barona Jaya. Methods: This quantitative study used a cross-sectional design and was conducted on 7–8 May 2026, involving 46 respondents drawn from a population of 85 students selected using a proportional sampling technique. Data on toothbrushing habits were collected through interviews using a questionnaire, while gingivitis status was assessed using the Gingival Index (GI) through clinical examination. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. Results: The majority of respondents had a poor toothbrushing habit (47.8%) and moderate gingivitis (41.3%). The Chi-Square test showed a p-value of 0.001 (p<0.05). Conclusion: Toothbrushing habits were significantly associated with gingivitis status among grade X students. School-based oral health education and periodic gingival examinations are recommended to improve preventive oral health practices among adolescents.